1979
DOI: 10.1002/1097-0142(197903)43:3<939::aid-cncr2820430323>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary melanoma

Abstract: From a series of 712 patients with melanoma, 38 patients (5.3%) had more than one primary melanoma. Twenty-four patients had two primaries, 11 patients had three, 2 patients had four, and l patient had eight. Twelve patients (32%) had one or more synchronous primaries. Forty-five percent of all multiple primaries were diagnosed within the first year. Microstaging by level and depth was determined prior to treatment and in patients with nonsynchronous primaries, 83% had a subsequent melanoma equal or less advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 17 publications
9
59
2
Order By: Relevance
“…Thus, the miniThe study data differed from the reported observations on several points. In contrast to the authors' findings, mum rate of ultra-late recurrence can be calculated to be 2.0% (20 though these women were also younger than their not the tendency for women to recur with regional involvement. From the literature, 64% of patients with male counterparts at the time of their primary diagnosis (36.6 years vs. 41.0 years), the disparity in age was lower extremity lesions had regional recurrence whereas all patients with truncal melanomas had disnot as great as that observed with patients in the current study.…”
Section: Resultscontrasting
confidence: 87%
“…Thus, the miniThe study data differed from the reported observations on several points. In contrast to the authors' findings, mum rate of ultra-late recurrence can be calculated to be 2.0% (20 though these women were also younger than their not the tendency for women to recur with regional involvement. From the literature, 64% of patients with male counterparts at the time of their primary diagnosis (36.6 years vs. 41.0 years), the disparity in age was lower extremity lesions had regional recurrence whereas all patients with truncal melanomas had disnot as great as that observed with patients in the current study.…”
Section: Resultscontrasting
confidence: 87%
“…3,6,7,9,12,[15][16][17][18][19][20] A study from the John Wayne Cancer Institute examined the first 2 primary melanomas in 114 patients with MPM who were identified from a melanoma database and demonstrated that there were significant differences between AJCC stage, mean tumor thickness, and Clark level of invasion between the first and second melanomas, and the second melanoma was thinner. 21 Our results indicating that the thickness of the first primary melanoma is significantly greater compared with the thickness of the second melanoma are consistent with previously reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have observed a better prognosis in patients who have MPM compared with patients who have SPM. 3,4,23 In a retrospective analysis on 5250 patients with melanoma that was controlled for known prognostic factors as well as ''survival bias'' (because patients who survive longer have the opportunity to develop additional tumors), the authors observed that patients who had !3 primary melanomas had longer survival than patients who had a single primary melanoma. 23 In another study, Ferrone et al suggested that less aggressive disease biology may be the reason for a higher percentage of disease-specific deaths in patients with SPM than in patients with MPM and also may be the reason for significantly thinner initial melanomas in patients with MPM versus patients with SPM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations